Integrasi Karakter Bangsa Berbasis Pendekatan Saintifik pada Perencanaan Pembelajaran IPS SMPN di Kecamatan Sape, Bima - Ida Waluyati; Irfan Irfan; Nurnazmi Nurnazmi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2019)
[Title: The Integrated of The Nations Characters Based on The Scientific Approach in the Lesson Plan of Social Science at SMPN in Sape Regions, Bima]. The rage of students delinquency that happens at Sape district, so the SMPN commit some efforts in designing the lesson plan of social science based on the scientific approach.The research aims to describe the integrity of the nations characters based on the scientific approach in social science planning at SMPN in Sape Regions, Bima. The study uses the descriptive qualitative approach. The subjects of the research are The headmaster, vice-headmaster and 6 teachers of IPS that are chosen purposively sampling. The instruments that are used: interview guide and documents. The technical analysis data that are used: reduction, display and verification. The testing of the data validity using the triangle source and tehcnics. The results results shows is sufficiently reprentative incarryng the values of nations characters in each level of RPP that made are the characteristic determinant of the achievement competency, the purpose of the study, learning methods, and technical evaluation of leraning in which continued by the program over the study result. Based on the results study, can be concluded thet the set of equipments which have been arranged have shown the learning activity by using the scientific approach and by integriting the characteristic values in every its component.